2008
DOI: 10.1002/bit.22066
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an enrichment process for circulating tumor cells from the blood of head and neck cancer patients through depletion of normal cells

Abstract: The optimization of a purely negative depletion, enrichment process for circulating tumor cells, CTC's, in the peripheral blood of Head and Neck cancer patients is presented. The enrichment process uses a red cell lysis step followed by immunomagnetic labeling, and subsequent depletion, of CD45 positive cells. A number of relevant variables are quantified, or attempted to be quantified, which control the performance of the enrichment process. Six different immunomagnetic labeling combinations were evaluated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
180
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 34 publications
2
180
0
3
Order By: Relevance
“…5 cells per h (∼10 4 cells detected for 6 min), which is sufficient for interrogating patient samples provided upstream enrichment strategies are used (e.g., CD45 depletion) (39,40). Therefore, in the future it may be feasible to use the SMR with constriction to identify CTCs in patient blood samples based on biophysical properties, which may reveal populations of CTCs that have gone undetected by common methods involving specific molecular probes.…”
Section: Characterizing Entry and Transit Velocities Of Cancer Cells mentioning
confidence: 99%
“…5 cells per h (∼10 4 cells detected for 6 min), which is sufficient for interrogating patient samples provided upstream enrichment strategies are used (e.g., CD45 depletion) (39,40). Therefore, in the future it may be feasible to use the SMR with constriction to identify CTCs in patient blood samples based on biophysical properties, which may reveal populations of CTCs that have gone undetected by common methods involving specific molecular probes.…”
Section: Characterizing Entry and Transit Velocities Of Cancer Cells mentioning
confidence: 99%
“…However, in addition to the TIMP-free active MT1-MMP enzyme, there is an excess of the latent proenzyme and the enzyme⅐TIMP inactive complexes on cell surfaces. Current detection methodologies, including immunocytochemistry, flow cytometry, and reverse transcription-polymerase chain reaction, do not discriminate among these MT1-MMP species and do not allow tracing of the cellular MT1-MMP activity (53). To specifically image the active MT1-MMP alone, we have previously developed genetically encoded FRET biosensors and showed that these biosensors were capable of visualizing MT1-MMP activity in live cells (54).…”
mentioning
confidence: 99%
“…An interesting approach with a negative CTC-enrichment technique was also developed utilizing the combination of viscous flow and magnetic force to facilitate the recovery of unlabeled cells (CTCs) from whole-blood samples obtained from cancer patients [76,77]. The method was based on removal of erythrocytes by lysis followed by the magnetic separation of immunomagnetically-labeled (with CD45 antibody) leukocytes.…”
Section: Article In Pressmentioning
confidence: 99%